Mechanism of the improvement of the energy of host–guest explosives by incorporation of small guest molecules: HNO3 and H2O2 promoted C–N bond cleavage of the ring of ICM-102 - Yiwen Xiao (Nature Portfolio, 2021)
Abstract Host–guest materials exhibit great potential applications as an insensitive high-energy–density explosive and low characteristic signal solid propellant. To investigate the mechanism of the improvement of the energy of host–guest explosives by guest molecules, ReaxFF-lg reactive molecular dynamics simulations were performed to calculate the thermal decomposition reactions of the host–guest explosives systems ICM-102/HNO3, ICM-102/H2O2, and pure ICM-102 under different constant high temperatures and different heating rates. Incorporation of guest molecules significantly increased the energy level of the host–guest system. However, the initial reaction path of the ICM-102 molecule was not changed by the guest molecules. The guest molecules did not initially participate in the host molecule reaction. After a period of time, the H2O2 and HNO3 guest molecules promoted cleavage of the C–N bond of the ICM-102 ring. Stronger oxidation and higher oxygen content resulted in the guest molecules more obviously accelerating destruction of the ICM-102 ring structure. The guest molecules accelerated the initial endothermic reaction of ICM-102, but they played a more important role in the intermediate exothermic reaction stage: incorporation of guest molecules (HNO3 and H2O2) greatly improved the heat release and exothermic reaction rate. Although the energies of the host–guest systems were clearly improved by incorporation of guest molecules, the guest molecules had little effect on the thermal stabilities of the systems.